2004
DOI: 10.1001/jama.291.21.2547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensive Handwashing Promotion on Childhood Diarrhea in High-Risk Communities in Pakistan

Abstract: EARLY 2 MILLION CHILDREN die annually from diarrheal disease. 1 A recent metaanalysis concluded that handwashing promotion interventions decrease diarrhea by a mean of 47%. 2 The authors estimate that such interventions could prevent 1 million child deaths per year. 2 However, the systematic meta-analysis and the studies it included summarized the reduction in diarrheal rates among all children or all family members. But all family members are not at equal risk of death from diarrhea. Children younger than 5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
225
3
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(249 citation statements)
references
References 21 publications
(30 reference statements)
5
225
3
7
Order By: Relevance
“…147 " 149 h. After contact with blood or bodily fluids. 213,214 i. After contact with the patient environment.…”
Section: S E C T I O N 4 : R E C O M M E N D E D H a N D H Y G I E N mentioning
confidence: 99%
“…147 " 149 h. After contact with blood or bodily fluids. 213,214 i. After contact with the patient environment.…”
Section: S E C T I O N 4 : R E C O M M E N D E D H a N D H Y G I E N mentioning
confidence: 99%
“…Moreover, the intervention had the major positive effects on those children who were suffering from moderate to severe malnutrition (statistics not provided in the evaluation study). 20 The study showed the positive hopes in the social and behavioural intervention of the diarrhoeal control in children. Luby et al in their follow up in 2009 reported that sustainability of the project was limited.…”
Section: Intervention 2: Intensive Hand Washing Promotion On Childhoomentioning
confidence: 85%
“…20 The incidence of diarrhoea was lowered by 53% (95 % CI, -65% to -41%) in the intervention areas. 20 The duration of illness was also reduced by 39% (counted in days).…”
Section: Intervention 2: Intensive Hand Washing Promotion On Childhoomentioning
confidence: 91%
See 2 more Smart Citations